Dynamics and Thermodynamics With Nuclear Degrees of Freedom
DOI: 10.1007/978-3-540-46496-9_15
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the giant dipole resonance properties with excitation energy

Abstract: The studies of the evolution of the hot Giant Dipole Resonance (GDR) properties as a function of excitation energy are reviewed. The discussion will mainly focus on the A ∼ 100 − 120 mass region where a large amount of data concerning the width and the strength evolution with excitation energy are available. Models proposed to interpret the main features and trends of the experimental results will be presented and compared to the available data in order to extract a coherent scenario on the limits of the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Second, there are changes in the configuration energies, along with the contribution of new configurations due to the thermal unblocking effect at finite temperatures. For open shell nuclei, 44 Ca exhibit a modest decrease, and a small increase is obtained for 56 Ca above the critical temperatures. We also note that the centroid energy decreases slightly for 52 Ca.…”
Section: A Ca Isotopesmentioning
confidence: 94%
See 1 more Smart Citation
“…Second, there are changes in the configuration energies, along with the contribution of new configurations due to the thermal unblocking effect at finite temperatures. For open shell nuclei, 44 Ca exhibit a modest decrease, and a small increase is obtained for 56 Ca above the critical temperatures. We also note that the centroid energy decreases slightly for 52 Ca.…”
Section: A Ca Isotopesmentioning
confidence: 94%
“…The experimental data on the GDR at finite temperature is mainly based on the study of the decay from fusion-evaporation reactions, which allow the production of self-conjugate compound nuclei (CN) at high excitation energy [40,41]. Despite being challenging experimentally, numerous studies have been carried out to investigate the T dependence of the dipole response, especially in the GDR region of highly excited nuclei [40][41][42][43][44][45][46][47]. Recent studies have shown that the GDR width has increased rapidly with temperature between 1 and 3 MeV; however, it gets saturated at much higher temperatures, which results in the gradual disappearance of giant dipole resonance due to excessive broadening [45,46].…”
Section: Introductionmentioning
confidence: 99%